Catholic Enlightenment for children. Teaching religion to children in the Habsburg Empire from Joseph II to the Restoration - Polenghi, Simonetta (Historia y Memoria de la Educación, 2016)
During Joseph II’s reign a deep cultural shift took place within the intellectual and religious establishment, with the acceptance of philosophical and pedagogical ideas that bore a distinctive Enlightenment and Protestant stamp. This cultural shift was applied to the teaching of religion by some relevant figures of the episcopal and pedagogical elites (J. A. Gall, F.M. Vierthaler, F. de Paula Gaheis, J. M. Leonhard). New handbooks and textbooks of the catechism were written which introduced new dialogic methods, more narrative, and borrowed Rochow’s typology of moral short stories. The content of Bishop Gall’s books was heavily rationalistic, whereas subsequent texts tried to balance reason and faith. Vierthaler, Gaheis, and Leonhard used a language that was more suitable for children and closer to the New Testament, with the use of parables and short stories. The so-called Socratic method was used in different ways by these authors. In the age of the Restoration, in spite of the process of school confessionalization, the heritage of the spirit of Enlightenment was still present, since by law the pedagogy taught in the Empire’s academic chairs and teacher training courses was the one defined by Milde, which bore a Kantian imprint, and stressed the importance of developing inner moral law in pupils. Leonhard was a follower of Milde, and his catechism, eventually approved for elementary schools for decades, bore this stamp. So at the end of the eighteenth and the beginning of the nineteenth centuries a new way of teaching religion was introduced, debated and contested in Habsburg Catholic territories. Rousseau’s and Salzmann’s theories were discussed; rationalism and faith, natural religion and revelation were confronted. In the end more attention was devoted to child psychology and language. The cultural fracture caused by Josephinism became less severe: orthodoxy was restored, but new pedagogical ideas actually entered the teaching of religion.